The Implications of a Backward Bending Labor Supply Curve - Krueger, Anne O. (Review of Economic Studies, 1962)
Journal Article The Implications of a Backward Bending Labor Supply Curve Get access Anne O. Krueger Anne O. Krueger Minneapolis Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 4, October 1962, Pages 327–328, https://doi.org/10.2307/2296309 Published: 01 October 1962